THE STATUS OF STRATIGRAPHY IN THE 21ST CENTURY - Dermitzakis, M.D (Bulletin of the Geological Society of Greece, 2010)
The 21st century geological time scale (GTS) will comprise an internationally agreed chronologic hierarchy. Correlation of events into the GTS will be undertaken using a wide variety of methods, including numeric dating, fossil occurrence, physical and chemical properties, tephrochronology and astrochronologic retrodictions. Chronostratigraphic subdivision of the sedimentary rock record should proceed in a bottom up hierarchical manner with lower units defining the boundaries of stratigraphically higher units. A moderate amount of work is required to improve the basis of the hierarchical subdivision of some Cenozoic series boundary subdivisions and to bring them in line with recommendations by the Stratigraphic Guide and recommendations by the International Committee of Stratigraphy (ICS).